2020
DOI: 10.1002/pc.25862
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the synergy influence of KSiCB and POE‐g‐MAH on mechanical properties of basalt fiber‐reinforced PA6 composites

Abstract: Silicon carbon black (SiCB), a kind of biomass carbon material, is a kind of pyrolysis ash prepared by anoxic pyrolysis of rice husk. When filled as an inorganic reinforcement in the composite material basalt fiber (BF) reinforced polyamide 6 (PA6), it has synergetic effect with the POE‐g‐MAH elastomer. Differential scanning calorimetry analysis shows that KSiCB plays a role of heterogeneous nucleation in the composite material, accelerates the nucleation and crystallization speed of PA6, and can increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…[1][2][3][4] However, this polymer has disadvantages, such as high humidity absorption, small resistance to crack propagation, high impact notch sensitivity, and low dimensional stability, which limit their use as a useful polymer in industrial sectors. [4][5][6][7][8][9] It is well known that fracture toughness affects the performance of polymers in various engineering applications. Therefore, the polymer toughening process has been an important and attractive topic for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, this polymer has disadvantages, such as high humidity absorption, small resistance to crack propagation, high impact notch sensitivity, and low dimensional stability, which limit their use as a useful polymer in industrial sectors. [4][5][6][7][8][9] It is well known that fracture toughness affects the performance of polymers in various engineering applications. Therefore, the polymer toughening process has been an important and attractive topic for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…So, we believed that the miscibility between POE‐g‐MAH and PA6 was better than that of POE‐g‐MAH and rCOC due to the good interaction between the amino groups in PA6 and the carboxyl groups in POE‐g‐MAH. [ 27–29 ]…”
Section: Resultsmentioning
confidence: 99%
“…So, we believed that the miscibility between POE-g-MAH and PA6 was better than that of POE-g-MAH and rCOC due to the good interaction between the amino groups in PA6 and the carboxyl groups in POE-g-MAH. [27][28][29] Meanwhile, it was found that the introduction of the elastic phase (POE-g-MAH) decreased the storage modulus of its blends. Because the mechanical strength of POE-g-MAH was much lower than that of PA6 and rCOC, the storage modulus of the blend dropped a little.…”
Section: Miscibility and Morphology Of The Compositesmentioning
confidence: 99%
“…[7][8][9][10] Based on this, basalt fibers have extensive applications in electrical equipment, petrochemical, construction, aerospace, automotive, and marine industries. 7,9,[11][12][13][14] While UV irradiation can result in the breakage of chemical bonds within composites, hastening the material's aging, the impact of UV radiation in diverse fields underscores the necessity for UV shielding materials that cover the full UV spectrum. This need spans various commercial applications, including UV-shielded windows, face masks, and more.…”
Section: Introductionmentioning
confidence: 99%